DEVELOPMENT OF ENVIRONMENTAL COMMUNICATION SKILLSIN STUDENT TEACHERS - Koshil , Oksana (The Modern Higher Education Review, 2022)
The article is devoted to the problem of formation of environmental communication skills among future teachers in the process of professional training. The psychological-pedagogical foundations of the formation of future educators’ environmental communication skills in the process of professional training are theoretically and methodologically substantiated. The article analyses the approaches of scientists to the interpretation of concepts that make up the scientific thesaurus of research: ‘ecological communication’, ‘ecological approach’, ‘ecological behaviour’, ‘ecological environment of the child’. The importance of ecological communication in the educational environment of a preschool education institution is substantiated. On the basis of the analysis of scientific works, the components of the studied education are distinguished: motivational, social, communicative, reflective; groups of technologies, effective non-traditional teaching methods are defined; methodological approaches of effective formation of skills to organize environmental communication with children of preschool age in a preschool education institution. The complex of pedagogical conditions for the effective formation of environmental communication skills in future educators in the process of professional training is characterized. It is proposed to modernize the pedagogical conditions for the formation of environmental communication skills among future educators through the implementation of coaching technologies during the pedagogical practices of students. The meaning of the concept of ‘ecological communication’ as non-violent communication, which includes awareness and respect for one’s own and others’ personal boundaries, self-love and care for one’s inner comfort, tolerance, acceptance of one’s own and others’ shortcomings, empathy, has been clarified. The fundamental principles of ecological communication in the educational environment of the preschool education institution are defined